El laberinto como símbolo del referente inexistente: una comparación entre Borges y Buzzativalkeborch - Coriasso, Cristina (Amaltea. Revista de Mitocrítica, 2009)
Borges, in the prologue of his Personal Library, establishing an analogy between Dino Buzzati and Kafka, has shown his admiration for the use of the fantastic thing in The Tartar Steppe (1940). Relying on this judgment and on the marked trend of an author as Borges to the integration of the different cultural materials on his own literary universe, we have compared, across the metaphor of the labyrinth as symbol of the non-existent modal, the story “The Two Kings and Their Two Labyrinths” (El Aleph), with I sette messaggeri, exordial story of La boutique del mistero. The idea of a universe like labyrinth temporary-space in which the man tries to introduce an order in the chaos, a finite structure that defines the infinite thing, a measurement of the time that annotates the eternal thing, sublies in both statements; nevertheless, beyond the skepticism with which Borges raises his philosophical cruxes, we find in Buzzati an attitude of opening to the mystery, of expectant interrogation, which impregnates his story of a deep lyricism.